IMPROVING THE PERFORMANCE PROPERTIES OF JET FUELS - Єфіменко, В. В.; Іванов, С. В.; Новікова, В. Ф.; Полякова, О. В. (Proceedings of National Aviation University (archive), 2021)
The issue of air solubility in jet fuels and its influence on the operation of fuel systems is considered. Experimental data on the change in the concentration of dissolved gases in RT fuel are presented. The optimal modes of its processing are selected and the results of gas saturation during storage are analyzed. A method of processing helium jet fuels in order to increase cavitation properties is proposed.